A time for truth : reigniting the promise of America - Cruz, Ted, 1970- (Broadside Books, an imprint of HarperCollinsPublishers, 2015)
A first book by the controversial senator outlines his political and personal perspectives while evaluating his potential for the 2016 GOP presidential nomination.